The NLRP3 inflammasome in ischemic stroke - Masenga, Sepiso K.; Kirabo, Annet (Frontiers in Stroke, 2024)
Ischemic stroke is a more common type of stroke and a leading cause of physical disability, cognitive decline, and death worldwide. Events occurring after an ischemic stroke episode determine the severity and outcomes. The NLR family pyrin domain containing 3 (NLRP3) inflammasome has emerged as a major contributor to the pathogenesis of ischemic stroke. Understanding its role in propagating ischemic injury is cardinal for therapeutic interventional research. In this review we summarize the current understanding of the underlying role of the NLRP3 inflammasome as well as highlight the current strides made in targeting the inflammasome as a modality to attenuate the effects of ischemic injury on brain tissue after a stroke event. We found that ischemic stroke initiates a cascade of complex intracellular processes beginning with oxidative stress that activates the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) consequentially activating the NLRP3 inflammasome. The NLRP3 inflammasome initiates inflammatory responses that exacerbate ischemic stroke. We have also briefly summarized the role of genetic susceptibility in stroke and its potential usage in clinical settings. Briefly, genetic mutations encoding the NLRP3 inflammasome are linked to stroke prognosis. A combination of advanced genetic testing and risk stratification based on sociodemographic, dietary, and lifestyle factors is encouraged for stroke prevention. IL-1 and IL-18 antagonists have been shown to inhibit the NLRP3 inflammasome consequently attenuating the adverse effects of ischemic stroke.